An Islamic Ecotheological Critique of Land Reclamation Practices in Manado City’s Regional Development Agenda - Ali Ridho; Erna Kurniawati; Rusdiyanto Rusdiyanto; Muhammad Tahir Alibe; Zainun Nur Hisyam Tahrus (Jurnal Masyarakat Maritim, 2026)
The Karangria coastal reclamation project in Manado Bay illustrates how regional development driven by spatial expansion and economic growth can conflict with environmental sustainability and social justice. This study examines the ecological, social, and governance implications of reclamation through the perspective of Islamic ecotheology. A qualitative case study design with critical analysis was employed. Primary data were collected through field observations, in-depth interviews, and documentation involving coastal residents, fishermen, religious leaders, academics, and relevant policymakers. Secondary data were obtained from policy documents, official reports, reputable academic publications, online news sources, and digital media. The findings show that reclamation has altered coastal landscapes, damaged marine habitats, reduced biodiversity, disrupted fishing grounds, and threatened the livelihoods of coastal communities. Limited public participation has also intensified inequality because local residents bear substantial environmental, social, and economic costs while development benefits remain concentrated among investors and politically influential groups. From an Islamic ecotheological perspective, these conditions indicate a departure from the principles of khalifah, amanah, mizan, maslahah, and the prevention of fasad. The study argues that regional development should not be assessed solely through investment, infrastructure, and economic indicators, but must also incorporate ecological responsibility, participatory governance, intergenerational justice, and protection for vulnerable coastal groups. Reclamation policy therefore requires stronger environmental assessment, transparent decision-making, meaningful community involvement, and continuous ecological monitoring. A participatory, inclusive, ethically grounded, and environmentally responsible development model is essential to reconcile regional progress with coastal sustainability and justice in Manado City. Safeguarding cultural continuity and community resilience for future generations.